Adenoid cystic carcinoma at base of the tongue with rare cervical lymph node metastasis diagnosed on fine needle aspiration cytology - Garg, Richa; Gupta, Sunil (International Journal of Scientific Reports, 2019)
Adenoid cystic carcinoma (ACC) is an uncommon malignant tumour of salivary glands. Occurrence at base of the tongue is rare. Distant metastasis is common, however, metastasis to regional lymph node is not seen commonly, but if occurs carries a bad prognostic value and lessens the average survival age of the patient. Fine needle aspiration cytology (FNAC) in such cases provides early diagnosis for rapid management of the patient. Review of literature shows that very occasional cases are reported with ACC at base of tongue with regional lymph node metastasis. Here, we present such a rare case of a 55 years old male patient with metastatic adenoid cystic carcinoma of cervical lymph node diagnosed on FNAC with primary at base of the tongue.